2010
DOI: 10.1001/archinternmed.2010.424
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Thyroid Dysfunction and Incident Hip Fracture in Older Adults

Abstract: Background Subclinical thyroid dysfunction is common in older adults and affects bone metabolism, but its effects on fracture risk have not been reported. We sought to determine prospectively whether older men and women with subclinical hyperthyroidism or hypothyroidism have an increased risk of hip fracture. Methods Prospective cohort of 3567 US community-dwelling adults, 65 years or older, with biochemically defined subclinical thyroid dysfunction or euthyroidism was enrolled from June 10, 1989, through Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 36 publications
1
101
1
3
Order By: Relevance
“…Several studies carried out in patients with iatrogenic hyperthyroidism showed that the risk for fracture was higher in older men and mainly in women with a very low TSH level (30,31,32). However, it is not totally clear that iatrogenic hyperthyroidism does affect bone in a totally similar way as hyperthyroidism due to toxic goiter or autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies carried out in patients with iatrogenic hyperthyroidism showed that the risk for fracture was higher in older men and mainly in women with a very low TSH level (30,31,32). However, it is not totally clear that iatrogenic hyperthyroidism does affect bone in a totally similar way as hyperthyroidism due to toxic goiter or autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…An increased risk in men but not women treated for hypothyroidism was also reported from observational studies in both the United Kingdom (17) and the United States. (18) Because the effects of more pronounced hypothyroidism include lowering of gonadotropin and sex hormone levels in otherwise eugonadal subjects, a state of mild or moderate central hypogonadism with low testosterone levels could ensue in men. (30) This could contribute to the observed increased fracture risk seen in younger and middle-aged men-an association that was absent in those >75 years old.…”
Section: Fig 2 Women Cumulative Duration Of Low Tsh (Hyperthyroid mentioning
confidence: 99%
“…Both overt hypothyroidism and hyperthyroidism have been associated with increased risk of fractures in previous studies (6,7,8,9,10,11,12,13,14). Other studies have reported that fractures are more common in persons with subclinical thyroid dysfunction (15,16), and some have found fracture incidence to increase by decreasing thyroid-stimulating hormone (TSH) within the reference range (13,17,18). However, the results of these and other studies are inconsistent (7,13,14,19,20).…”
Section: Introductionmentioning
confidence: 99%